KONTRIBUSI PENDAPATAN IBU RUMAH TANGGA TERHADAP KELUARGA PETANI DI DESA KIE ICI KECAMATAN IBU KABUPATEN HALMAHERA BARAT - Astrodein ., Sawangponto; Vicky Richard B. Moniaga; Ribka Magdalena Kumaat (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine the contribution of housewives to the income of farmer families in Kie ici Village, Mother District, West Halmahera Regency. This research was conducted for three monthsfrom October to December 2018. Data collection methods used were primary data and secondary data. The data taken is primary data using direct interview techniques and questionnaires for 30 farmer housewives. While secondary data was obtained from the Kie ici Village office, books available in stores and the internet such as google cendekia to access articles from various scientific journals and theses from other universities related to the topic of this research namely the contribution of housewives to the family. The results showed that the contribution of housewives' income to farmer households in Kie ici village in general housewives were able to contribute, at 39.68 percent, to family income which could be categorized as sufficiently fulfilling the family's need to live.*eprm*